Understanding The Meaning Of Mathal In Kalilah Wa Dimnah Using Malay Proverb - Tuan Mat, Nik Norimah; Abd Rahman, Noor Eliza; Che Mat, Azman (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2025)
Translating figurative language in literary work is not an easy task. Mathal is a figurative language in Arabic that is used widely in Arabic literary works. This paper intends to analyze the translation of mathal in Kalilah wa Dimnah to Malay and examine the equivalence meaning of mathal with Malay proverbs. This is a qualitative study using the content analysis method. The research material of this study is the Arabic literary work, namely Kalilah wa Dimnah. Nine (9) samples of data were chosen purposively from the book. This study aims to analyze the translation of mathal in Kalilah wa Dimnah based on metaphor translation strategies proposed by Newmark (1988). To find the equal Malay proverbs with similar meaning, the data were compared contrastively by referring to Kamus Istimewa Peribahasa Melayu (KIPM). The findings revealed that the translator likely tends to use the literal strategy in translating mathal to Malay. The target readers can understand the translation. However, these translations are less culturally connected to the readers. Therefore, it is suggested to add the equivalent proverb in the target language to maintain the stylistic impact from the source language to the target language. This strategy can preserve the meaning and context embedded within the proverb. This paper demonstrated the equivalence of mathal and Malay proverbs regarding meaning. Translators must consider this aspect in translating proverbs to convey the intended meaning effectively in the target language. This study indicates the significance of cultural equivalence in translating literary work. The findings of this study benefit translators in the field of Arabic-Malay translation and improve the understanding of mathal using Malay proverbs, especially among non-Arabic speaking students.